A switch to endoscopic mucosal resection after precutting following gastric perforation during endoscopic submucosal dissection: a simple and useful technique - Lee, D. W.; Lee, H. S.; Jung, M. K.; Kim, S. K.; Jeon, S. W. (Endoscopy, 2012)
Endoscopic submucosal dissection (ESD) is safe and effective, but as the number of patients undergoing ESD has increased, so has the number of iatrogenic perforations. We describe the effectiveness and benefits of endoscopic mucosal resection after precutting (EMR-P) in a series of patients who developed a macroperforation during ESD. This was a retrospective, single-center case series from a prospectively maintained database in an academic tertiary care center. The study involved 16 patients with macroperforation out of 1171 patients who underwent ESD between November 2006 and January 2011. En bloc resection by EMR-P was achieved in 12 out of 16 patients (75 %) and piecemeal resection in 4 (25 %). All patients were discharged after a mean hospital stay of 6.8 days without further complications. There were no recurrences during the median follow-up period of 11.4 months. Macroperforation during ESD can be managed successfully by endoscopic closure, and EMR-P should then be considered.